Peran Unicef dalam Peningkatan Program Pendidikan di Kabupaten Sorong 2010-2013 - , Febe Maryona Tahitu, Drs. Muhadi Sugiono, MA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Special Autonomy for Papua imposed by Act No. 21 of 2001 is a valuable strategic policy in improving care, accelerating the development and empowerment of the people of Papua, because it is expected to increase in many areas of community life including education. Related to this, the problem of education has also become the world's attention in accordance with the objectives of Millennium Development Goals (MDGs) to 2, namely primary education for all. UNICEF supports the implementation of programs of the Millennium Development Goals (MDGs). UNICEF is realized through a variety of programs in Sorong Regency. UNICEF has run SBM (School Based Management) in Sorong Regency, which include school management, teaching methods, and the active role of the community. UNICEF direct role in memonitioring, evaluate, and provide technical assistance in the form of provision of equipment and relief funds. The program has been running optimally and to bring important changes to education in Sorong Regency. Moreover, the involvement of local governments in the success of the program perlaksanaan. The results of the UNICEF program of cooperation with the local government district of Sorong broadly seen by looking at changes in physical and non-physical state of schools in the districts of Sorong post UNICEF program in 2010 until now. UNICEF and Sorong regency administration is mutually beneficial cooperation. UNICEF in the sense that without the program, Sorong districts tend not to increase the quality of education, on the other hand without the UNICEF regional government is not necessarily to run the program properly and successfully. The author notes that in the form of mutually beneficial cooperation is further clarified with the safety situation in the districts of Sorong. UNICEF works because of political stability and security in the district either sliding. It is not separated from the role of local government.